2021
DOI: 10.1007/s11356-021-14849-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold exposure and capsaicin on the expression of histone acetylation and Toll-like receptors in 1,2-dimethylhydrazine-induced colon carcinogenesis

Abstract: Previous studies have indicated that capsaicin-rich diet and cold weather have showed strong association with tumor incidence. Thus, we investigated the effects of capsaicin and cold exposure in 1,2-dimethylhydrazine-induced colorectal cancer as well as the mechanisms underlying capsaicin and cold induced CRC. Rats were randomly divided into four groups and received cold still water and capsaicin via intragastric gavage until the end of the experiment. The rat's body weight, thymus weight, and food intakes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The DMH exerts its effects by damaging the mucus, methylating the tissue, and forming free radicals [ 50 ]. In addition, it is shown that oral antioxidants can decline the effects and lesions caused by DMH [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DMH exerts its effects by damaging the mucus, methylating the tissue, and forming free radicals [ 50 ]. In addition, it is shown that oral antioxidants can decline the effects and lesions caused by DMH [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered that TLR2 expression was much elevated in CRC patients, and this had an impact on patient survival. TLR2 stimulation increased the migration, invasion, and proliferation of CRC cells 184–187 . Furthermore, the gut flora contribute significantly to the advancement of CRC, and Fusobacterium nucleatum enhances the development of CRC by upregulating the expression of inflammatory mediators via TLR2 signaling 188,189 .…”
Section: Tlr‐related Diseasesmentioning
confidence: 99%
“…The expression of TLRs is elevated in multiple cancer types, such as those affecting the liver, intestinal tract, and oral cavity. These receptors are essential for the development and spread of malignant tumors as well as the prognosis of cancer 170–173,184–187,202,231–236,319,320 . TLRs promote carcinogenesis by inducing different cells to release proinflammatory cytokines and antiapoptotic factors, recruiting immune cells, and promoting cell proliferation in TME, thereby creating a tumor‐friendly environment.…”
Section: Clinical Therapy Involving Tlrsmentioning
confidence: 99%
See 2 more Smart Citations